Exploring the Impact of Collaborative Learning and Student Engagement on Student Learning Performance: A Comprehensive Analysis of Influencing Factors - Mudrikah, Saringatun; Pitaloka, Lola Kurnia; Kardiyem; Setiyani, Rediana (Economic Education Analysis Journal, 2024)
This research deepens how social factors influence collaborative learning and student engagement, ultimately influencing student learning performance. This research is a type of quantitative research with a causality approach. The research population is economics education students. The sampling method uses a proportional random technique and the number of samples used was 206 students. The data collection instrument uses a questionnaire. The data analysis technique used was a structural equation model (SEM-PLS). The research results showed that interaction with peers had a positive effect on collaborative learning, student-lecturer interaction had no effect on collaborative learning, social presence had a positive impact on collaborative learning, use of social media had no effect on collaborative learning, cooperative learning had a positive impact on student engagement, Student engagement has a positive influence on student learning performance, Collaborative learning mediates the relationship between social factors (i.e. social interaction (with peers), student-lecturer interaction, social presence, use of social media) and student engagement, Student Engagement mediates the relationship between factors social, collaborative learning, and student learning performance. This research has several limitations, research considers four social factors that influence active collaborative learning; therefore, future research should include other variables, such as student involvement or use learning outcomes as the dependent variable.